Nose-to-Brain Therapeutics in Parkinson’s Disease: Clinical Trials, Mechanisms, and Therapeutic Potential - Emily Cherny; Tamara Minko (Pharmaceutics, 2026)
Background/Objectives: Intranasal delivery is a promising noninvasive approach to enhance central nervous system drug delivery in Parkinson’s disease (PD), potentially bypassing the blood–brain barrier and minimizing gastrointestinal side effects. This review summarizes clinical trials and translational evidence for intranasal PD therapies by treatment options and intent, highlighting key challenges in efficacy, pharmacokinetics, and safety. Methods: We reviewed human clinical trials, preclinical and pilot studies, and pharmacokinetic investigations of intranasal therapies for PD. Comparisons to established treatments were included in context. Only PD-specific clinical studies were analyzed. Therapies were grouped by rescue, antioxidant/metabolic/hormonal, and biologic or cell-based approaches, with continuous-delivery systems reviewed separately. Results: Intranasal rescue therapies, such as apomorphine, provide rapid improvement during OFF episodes (periods when the effects of PD medications fade and symptoms reappear), but tolerability issues and nasal irritation limit usage. Early-phase studies suggest intranasal delivery enables quick symptom relief and favorable pharmacokinetics, though most trials are small and focus on feasibility. New approaches include antioxidants, neurotrophic factors, gene therapy, and cell-based methods, with advanced formulations enhancing nasal retention and brain uptake. However, more translational evidence and long-term safety data are needed. Conclusions: Intranasal therapies for PD offer rapid rescue and expand options beyond standard drugs. Large, well-designed trials are needed to confirm efficacy, long-term safety, and optimal formulations. Intranasal delivery remains an emerging but potentially transformative strategy requiring further clinical research.